One Point Technique of Intracutaneous Sterile Water Injection is as Effective as Four Points Technique in the Management of Labor Pain - Ismail, Taufik (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To compare the score of VAS (visual analog scale), length of labor, and APGAR score in intracutaneous sterile water injection between one point technique and four points technique at Michaelis Rhomboid area in management of labor pain. Method: This is an experimental study, subjects were included by blinded controlled randomized study on 50 women with term pregnancy stage I active phase and were planned for spontaneous delivery. Subjects were divided into 2 groups randomly, 25 women with 0.5 ml sterile water intracutaneous injection on 4 points and 25 women with that on 1 point injection at one site at the painful area. Result: Reduction of labor pain on 1-point technique could decrease VAS score the most, 85.4 (4.3) into 48.4 (8.5) on minute 10. Length of labor was 11.2 (1.15) on 1 point injection group compared to 11.4 (1.2) on those with 4 point injection. On the other hand, APGAR score of the baby on group having 1-point injection was 7.86 (0.5) on min 1 and 9.68 (0.5) on min 5, compared to that on 4-points injection group, 7.52 (0.7) and 9.56 (0.5), respectively. In addition, 60% felt uncomfortable with 1-point injection whereas 80% of patients felt uncomfortable in 4-points injection. Conclusion: There is no significant difference on reduction of VAS score, duration of labor, and APGAR score of the baby between the group having 1 point injection and 4-point injection. However, injection on 1 point is more comfortable. [Indones J Obstet Gynecol 2012; 36-4: 167-70] Keywords: APGAR , intracutaneous sterile water injection, length of labor, VAS